Formulation of Spinach Leaf Extract (Amaranthus tricolor L.) Shampoo and Antifungal Activity Test Against Pityrosporum ovale - Margareta Retno Priamsari; Marcia Angelica Vidigal Loi Pinto; Nanda Dwi Akbar (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Red spinach leaves contain flavonoid, tannin, alkaloid, saponin and terpenoid that have potential as antifungal compounds. This research is  experimental. The purpose of this reserach is is to find out extract red spinach leaves can inhibit the growth of Pityrosporum ovale and to find out that red spinach leaf extract can be formulated in shampoo. Extraction was carried out using the remaceration method with 70% ethanol solvent and then tested for phytochemical content. Antifungal activity testing of red spinach leaf extract using concentrations of 15; 30; 45; 60 and 75% using the well method with PDA media incubated at 37 for 3x24 hours. The results showed the average inhibition zone activity against Pityrosporum ovale at a concentration of 75% of 19.17 mm statistically showed a significant difference. Formulation of shampoo preparations was carried out on red spinach leaf extract at a concentration of 15% with variations in the formula of Cocamide DEA and CMC-Na. The physical characteristics of the shampoo preparation include organoleeptic test, homogeneity, pH, viscosity, adhesion, spreadability and foam height. The results of testing the antifungal activity of shampoo preparations in formula 1 (17.5 mm); formula 2 (17.83 mm); and formula 3 (16.83 mm), based on statistical tests of antifungal shampoo preparations with a p-value (> 0.05) variations in the concentration of Cocamide DEA and CMC-Na have no significant effect on antifungal activity.